Impact of Organizational Readiness, Management Support, and Fintech on MSMEs Supply Chain Performance - Zulhelmy M. Hatta; Firdaus AR; Ruhul Fitrios; Dani Pratama (Universitas Hayam Wuruk Perbanas, 2025)
Micro, Small, and Medium Enterprises (MSMEs) play a pivotal role in Indonesia’s eco-nomic stability, as demonstrated by their resilience during the 1998 economic crisis. This study examines the influence of organizational readiness, top management support, and financial technology on the supply chain performance of MSMEs in Pekanbaru, with the success of Accounting Information Systems (AIS) serving as a mediating factor. A pur-posive sample of 190 MSMEs was analyzed using Structural Equation Modeling-Par-tial Least Squares (SEM-PLS). The findings indicate that organizational readiness, top management support, and the success of Accounting Information Systems significantly enhance supply chain performance. In contrast, financial technology does not have a di-rect impact on supply chain performance. However, organizational readiness, top man-agement support, and financial technology all positively contribute to the success of Ac-counting Information Systems. Theoretical implications of this study reinforce the Re-source-Based View (RBV) and the DeLone & McLean Information System Success Model, emphasizing the importance of organizational readiness and top management support in improving supply chain performance through the success of Accounting In-formation Systems. Additionally, this research contributes to the literature on financial technology within the framework of the Technology Acceptance Model (TAM), high-lighting its potential to enhance supply chain integration and efficiency in MSMEs. These insights provide practical strategies for MSMEs to optimize their supply chain management by effectively leveraging organizational and technological resources.